Perjudian Online di Kalangan Mahasiswa Ditinjau dari Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transasksi Elektronik - I Kadek Puji Astawa (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The phenomenon of online gambling among students has become a serious legal and social issue that requires greater attention from educational institutions, families, and law enforcement authorities. The rapid development of digital technology and internet accessibility has made online gambling platforms easier to access, increasing the risk of student involvement in unlawful activities. This article aims to analyze the legal provisions governing the crime of online gambling under Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE Law) and to examine the criminal liability of students who engage in online gambling activities. This study employs a normative juridical method using a statutory approach and an extensive literature review to examine relevant laws, legal doctrines, and previous studies. The findings indicate that online gambling constitutes a prohibited act as stipulated in Article 27 paragraph (2) of the ITE Law and may result in criminal sanctions for individuals involved. Furthermore, the study reveals that the increasing prevalence of online gambling among students is influenced by easy internet access, limited parental and institutional supervision, financial motives, peer influence, and insufficient awareness of the legal consequences associated with such activities. Therefore, more comprehensive preventive measures are necessary through collaboration among universities, families, government institutions, and law enforcement agencies. Public education, digital literacy programs, and stricter law enforcement are expected to reduce student participation in online gambling and foster greater legal awareness within the academic community.